Cerebrospinal fluid oligoclonal immunoglobulin gamma bands and long-term disability progression in multiple sclerosis: a retrospective cohort study - Virginija Danylaité Karrenbauer; Sahl Khalid Bedri; Jan Hillert; Ali Manouchehrinia (Scientific Reports, 2021)
Abstract Multiple sclerosis (MS) patients with immunoglobulin gamma (IgG) oligoclonal bands (OCB) in the cerebrospinal fluid (CSF) have different genetic backgrounds and brain MRI features compared to those without. In this study, we aimed to determine whether CSF-OCB status is associated with long-term disability outcomes. We used Swedish MS register data on clinically definite MS patients with known OCB status. Date of birth, age at MS onset, and time to sustained Expanded Disability Status Scale (EDSS) milestones 3, 4, and 6; time to conversion to secondary progressive (SP) MS, sex, and immunomodulatory treatment (IMTs) duration were collected. Multivariate Cox regression models were used to investigate the association between OCB status and risk of reaching each milestone. The OCB-positive group reached disability milestones at an earlier time and younger age. OCB-positivity significantly increased the risk of reaching EDSS 3.0 (HR = 1.29, 95% CI 1.12 to 1.48, P < 0.001) and 4.0 (HR = 1.38, 95% CI 1.17 to 1.63, P < 0.001). The OCB-positive group had a 20% higher risk of conversion to SPMS. CSF-OCB presence is associated with higher risk of reaching EDSS milestones and conversion to SPMS. Our findings suggest higher disease modifying effect of OCB presence in the early inflammatory stages of MS.